INSTRUCTIONAL MATERIALS DESIGN AND DEVELOPMENT OF ENGLISH POETRY CLASS - Rizal, Sarif Syamsu (Jurnal Bahasa Inggris, 2017)
The inspiring issue to share this paper is to increase teachers? responsibilities as more than just transferring knowledge, distributing scientific facts, and becoming a useful model for learners but teachers have to be able to design and develop learners through engaging in any learning opportunities, search out and construct meaningful educational experiences that allow them to solve real-world problems and show that they have learned big ideas, powerful skills, and habits of mind also heart that meet educational standards as being stated at ELT Today in Global Community, 2017.This paper entitles ?Instructional Materials Design and Development of English Poetry Class? revealing what to prepare and what to conduct, that later on being called as Two-Whats- To-Do, in teaching English poetry. To implement it in learning process; learners are going to recognize and practice how to analyse poetry to develop intellectual skill and how to write poetry to motivate creativity skill. By achieving these skills, the learners are able to apply capabilities; those are literary research and creative writing especially on English poetry.In composing this paper, the writer used qualitative descriptive in what factors have to be prepared in teaching English poetry to learners. The result of the study describes the factors namely planning and conducting in teaching-learning process based on the Revised Bloom?s Taxonomy. To develop and implement the Two-Whats- To-Do in teaching English poetry are expected to be the objectives after finishing the process such as learners understand the importance of literary work for life, learners are interested in poetic interpreting and creative writing in all part of excitement and mystery of learning English poetry, and learners express their thoughts, ideas, questions while attempting to interpret a poem. The benefit of the paper is that the Two-Whats- To-Do in teaching English poetry can be a usefulmodel to English literature teacher, learners, devotees, observers, and translators.